Bacterial Division Proteins FtsZ and ZipA Induce Vesicle Shrinkage and Cell Membrane Invagination - Cabré, Elisa J. (American Society for Biochemistry and Molecular Biology, 2013)
Permeable vesicles containing the proto-ring anchoring ZipA protein shrink when FtsZ, the main cell division protein, polymerizes in the presence of GTP. Shrinkage, resembling the constriction of the cytoplasmic membrane, occurs at ZipA densities higher than those found in the cell and is modulated by the dynamics of the FtsZ polymer. In vivo, an excess of ZipA generates multilayered membrane inclusions within the cytoplasm and causes the loss of the membrane function as a permeability barrier. Overproduction of ZipA at levels that block septation is accompanied by the displacement of FtsZ and two additional division proteins, FtsA and FtsN, from potential septation sites to clusters that colocalize with ZipA near the membrane. The results show that elementary constriction events mediated by defined elements involved in cell division can be evidenced both in bacteria and in vesicles.